PEMIDANAAN TERHADAP PELAKU PERMUFAKATAN JAHAT DAN PERCOBAAN UNTUK MELAKUKAN TINDAK PIDANA TERORISME - rahmad sujud; Muhammad Hendra Razak; Herman Sitompul; Bagus Irawan (Universitas Tangerang Raya, 2021)
Terrorism is a crime against humanity and human civilization and is a serious threat to humanity and human civilization and a serious threat to the integrity and sovereignty of a country. or a danger to security, peace and is very detrimental to the welfare of the community and nation. The author provides examples of cases of criminal conspiracy, trials, or assistance to commit criminal acts of terrorism. The formulation of the problem that will be discussed by the author is: How is the form of evil conspiracy that can be categorized as an attempted criminal act of terrorism. Finally, based on the results of the study, the author concludes that the form of evil conspiracy that can be categorized as an attempted criminal act of terrorism is that all preparations for a criminal act of terrorism can be interpreted as preparation/trial of a terrorist act which prepares all efforts for the occurrence or implementation of terrorism acts, both physically, financially and others. -other things that increase the possibility of the success of a criminal act of terrorism, such as any person who intentionally organizes, provides, or participates in military training, paramilitary training, or other training, both domestically and abroad, with the intention of planning, preparing, or commits a criminal act of terrorism, or any person who intentionally provides or collects funds with the aim of being used or knowingly will be used partially or wholly to commit a criminal act of terrorisme